Financing the European Green Deal - Šajdíková, Lucia (2022)
The purpose of this bachelor thesis is a descriptive analysis of financing the European Green Deal. It is divided into several parts. The first part describes the institutional framework of the European Green Deal, such as the European Investment Plan, which identifies allocations of funds in the EU Member States. The second part then identifies public financing supporting the green economy, and the third part identifies commercial funding. The last chapter is focused on the Czech Republic.